Small farm mechanization in rainfed based cropping system for drudgery reduction and livelihood security - Basavaraju, Sanjeeva Reddy; Nirmala, G; Pankaj, P K; Ravishankar, K; Reddy, A G K; Nagasree, K; Reddy, K Sammi; Ram, L B Thulasi; Chary, G Ravindra (Indian Farming, 2019)
In India, about 60% of net sown area is under rainfed agriculture and the rainfall majorly scripts the people’s livelihoods. The poor fertility status of soil and lower moisture holding capacity further make the rainfed farming more complex. There is an urgent need to address small farm mechanization aspects of the farmers to meet the timeliness of operations, reduce drudgery and enhance the input use efficiency to improve the productivity from rainfed agriculture. In this study, need based improved agricultural implements and small scale machinery were introduced to farmers and its utility was assessed in a cluster approach mode in Pudur mandal, Telangana. The results showed that, interventions reduced the drudgery load. The selected set of implements saved time and cost through reducing physical work load and altering working posture. Small farm mechanization not only increased the labour productivity by reducing drudgery, but also helped in bringing more area under cultivation and enhances the farm holder’s livelihoods security.